A TALE OF THREE REGIONS: QUALITY CULTURE AND ITS IMPACT ON PHARMACEUTICAL PRODUCTION - Swartz, Bronwyn; Singh, Shalini (The South African Journal of Industrial Engineering, 2022)
This study presents a comparative literature examination of the pharmaceutical industry in Japan, Europe, and the United States, focusing on quality culture, which historically has impacted operations in these regions. It aims to highlight generic pitfalls that result from cultural influences so that these can be avoided when designing a conceptual model of quality management practices for South African organisations. Simultaneously, the literature illuminates areas where culture promotes operational excellence (OpEx) in production. Quadrants of the organisational cultural analysis instrument (OCAI) are used to collect and examine research data from 72 literature sources. An activity theory research approach is adopted to perform a comparative study to ensure a consistent formal examination of the three geographical regions. During this analysis, industry traits presumed to be supported by culture types are highlighted and examined. Findings from this examination will be used in a future study to develop an OpEx model for South Africa, based on quality culture.